Santa Sede e debito illegittimo.Il cammino verso la Corte internazionale di giustizia (2015-2022) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Il discorso del Santo Padre Francesco (Santa Sede in senso proprio) ai membri dell’Assemblea Generale dell’Organizzazione delle Nazioni Unite - 2. La posizione della Santa Sede in senso lato e dei vertici della Chiesa italiana - 3. Odierne prospettive nella linea di lavoro politico - 4. La via africana sul debito - 5. Argentina e Fondo Monetario Internazionale (FMI).Holy See and illegitimate debt. The path to the International Court of Justice (2015-2022)ABSTRACT: This work offers a synthesis of the main steps of the process towards the International Court of Justice, accomplished over a seven-year period by the Holy See and the Cartel of jurists inspired by the Charter of Sant’Agata de’ Goti – Declaration on Usury and International Debt (1997). The starting point is Holy Father Francis’ speech at the United Nations General Assembly (New York, September 25, 2015), where the devastating deviations of speculative finance were condemned. Next, the points of convergence with the positions taken on the matter by the Italian Bishops’ Conference (CEI) are described, as well as today’s perspectives on debt and the International Court of Justice, in the line of political engagement, with regard to the Gentiloni government and the first Conte government. Completing the discussion is a report on what the author calls the African way on debt and an in-depth look at the differences from a recent wide-ranging initiative aimed at resolving the long-standing issue of the Argentine debt.